Binding of Shewanella FadR to the fabA fatty acid biosynthetic gene: implications for contraction of the fad regulon. Issue 9 (7th June 2015) - Zhang, Huimin; Zheng, Beiwen; Gao, Rongsui; Feng, Youjun
Abstract: The Escherichia coli fadR protein product, a paradigm/prototypical FadR regulator, positively regulates fabA and fabB, the two critical genes for unsaturated fatty acid (UFA) biosynthesis. However the scenario in the other Ɣ–proteobacteria, such as Shewanella with the marine origin, is unusual in that Rodionov and coworkers predicted that only fabA (not fabB ) has a binding site for FadR protein. It raised the possibility of fad regulon contraction. Here we report that this is the case. Sequence alignment of the FadR homologs revealed that the N-terminal DNA-binding domain exhibited remarkable similarity, whereas the ligand-accepting motif at C-terminus is relatively-less conserved. The FadR homologue of S. oneidensis (referred to FadR_she) was over-expressed and purified to homogeneity. Integrative evidence obtained by FPLC (fast protein liquid chromatography) and chemical cross-linking analyses elucidated that FadR_she protein can dimerize in solution, whose identity was determined by MALDI-TOF-MS. In vitro data from electrophoretic mobility shift assays suggested that FadR_she is almost functionally-exchangeable/equivalent to E. coli FadR (FadR_ec) in the ability of binding the E. coli fabA (and fabB ) promoters. In an agreement with that of E. coli fabA, S. oneidensis fabA promoter bound both FadR_she and FadR_ec, and was disassociated specifically with the FadR regulatory protein upon the addition of long-chain acyl-CoA thioesters. To monitor in vivo effect exerted by FadR on Shewanella fabA expression, the native promoter of S. oneidensis fabA was fused to a LacZ reporter gene to engineer a chromosome fabA-lacZ transcriptional fusion in E. coli . As anticipated, the removal of fadR gene gave about 2-fold decrement of Shewanella fabA expression by β-gal activity, which is almost identical to the inhibitory level by the addition of oleate. Therefore, we concluded that fabA is contracted to be the only one member of fad regulon in the context of fatty acid synthesis in the marine bacteria Shewanella genus.